Solar Cells Based on Colloidal Nanocrystals - Borchert, Holger; SpringerLink (Online service) (London: Springer, 2014)
This book presents a new system of solar cells. Colloidal nanocrystals possess many physical and chemical properties which can be manipulated by advanced control over structural features like the particle size. One application field is photovoltaics where colloidal semiconductor nanocrystals are explored as components of photo-active layers which can be produced from liquid media, often in combination with conductive polymers. The further development of this interdisciplinary field of research requires a deep understanding of the physics and chemistry of colloidal nanocrystals, conducting polymers and photovoltaic devices. This book aims at bridging gaps between the involved scientific disciplines and presents important fundamentals and the current state of research of relevant materials and different types of nanoparticle-based solar cells. The book will be of interest to researchers and PhD students. Moreover, it may also serve to accompany specialized lectures in related areas.
Introduction -- Materials -- Characterization of Thin Polymer Films and Nanocrystals -- Solar cells with Colloidal Nanocrystals.
0
Keywords: Chemistry, Physical organic; Engineering; Optical materials; Materials Science; Optical and Electronic Materials; Nanoscale Science and Technology; Physical Chemistry; Nanotechnology and Microengineering; Optics and Electrodynamics; Semiconductors